c - Ibn Kathir, Ismail Ibn Umar (Lahore Darussalam, 2010)
Miracles & Merits of Allah's Messenger By Ibn Katheer The book then discusses the blessed and beautiful characteristics and merits of the Prophet and then goes on to describe the miracles that he performed. Ibn Katheer than compares the miracles given to Prophet Muhammad with those that were given to the other Prophets; he then shows that Prophet Muhammad collectively received the same miracles that were granted to the other Prophets separately. AI-Bidayah wan Nihayah (The Beginning and The End), by the renowned scholar Abu Al-Fida 'Imad ad-Deen Isma'eel bin 'Umar ibn Katheer, is considered as one of the most authoritative sources on Islamic History.
Keywords: Islam -- History -- Early works to 1800